2022
DOI: 10.1038/s41598-022-26038-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of learning weakness from drawing analysis at the pre-literacy stage

Abstract: Handwriting learning delays should be addressed early to prevent their exacerbation and long-lasting consequences on whole children’s lives. Ideally, proper training should start even before learning how to write. This work presents a novel method to disclose potential handwriting problems, from a pre-literacy stage, based on drawings instead of words production analysis. Two hundred forty-one kindergartners drew on a tablet, and we computed features known to be distinctive of poor handwriting from symbols dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In detail, the two vectors of the latent representation, i.e., pulsations and phases with i = 1, …, s , and the vector of weights of the decoder’s layer, representing the importance of each of the sinusoids found by the network, i.e., with i = 1, …, s . Since the most discriminative features for the identification of handwriting difficulties are those related to frequency [ 11 ], the linear component of Time2Vec, i.e., the component corresponding to i = 0, was excluded from the extracted feature set and used only at the reconstruction stage.…”
Section: Methods and Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In detail, the two vectors of the latent representation, i.e., pulsations and phases with i = 1, …, s , and the vector of weights of the decoder’s layer, representing the importance of each of the sinusoids found by the network, i.e., with i = 1, …, s . Since the most discriminative features for the identification of handwriting difficulties are those related to frequency [ 11 ], the linear component of Time2Vec, i.e., the component corresponding to i = 0, was excluded from the extracted feature set and used only at the reconstruction stage.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…Recently, Dui et al [ 11 ] confirmed the effectiveness of deep learning in the context of dysgraphia prevention even before handwriting is learned. Using serious games from the iPad application Play-Draw-Write, the authors collected data from children in the last year of kindergarten, and through the use of a convolutional neural network called LearNet, they were able to effectively discriminate between “at-risk” and “non-at-risk” children.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of affordable digital tablets over the past decade has created new opportunities for identifying cognitive and motor control differences among populations through drawing, tracing, and handwriting tasks [1][2][3][4][5][6][7][8][9][10][11][12]. Compared to conventional penand-paper assessments, which limit analysis to the final product, tablet computers allow researchers to study the process of drawing by capturing continuous changes in pen position, pen-on-tablet pressure, and the stylus azimuth or tilt.…”
Section: Introductionmentioning
confidence: 99%